PENINGKATAN KINERJA GURU DALAM MELAKSANAKAN PEMBELAJARAN YANG EFEKTIF MELALUI SUPERVISI OBSERVASI KELAS DI SDN JERUK SOKSOK 3 KECAMATAN BINAKAL TAHUN SEMESTER GANJIL PELAJARAN 2022-2023: SDN JERUK SOKSOK 3 KECAMATAN BINAKAL TAHUN SEMESTER GANJIL PELAJARAN 2022-2023 - ALI WAFA (Dewan Pendidikan Bondowoso, 2022)
One of the duties of the Principal is to carry out supervision in the school which is his responsibility. To carry out effective supervision of class observations requires conceptual, interpersonal and technical skills. Therefore, every school principal must own and master the concept of classroom observation supervision which includes: definition, purpose and function, principles, and substance dimensions of class visit supervision. One of the efforts made by the principal in improving the quality of education is through improving teacher performance in the teaching and learning process which is carried out through fostering supervision of the principal's class observation. The purpose of this school action research is to find out how far teacher performance has increased in carrying out effective learning at SDN Jeruk Soksok 3 through classroom observation supervision. In this action research conducted in 3 cycles, the results of the actions taken proved to be able to improve teacher performance by achieving ideal standards. The results of this school action research show that the implementation of the principal's class observation supervision can improve teacher performance with completeness reaching 100%, the teacher's response is very positive towards the guidance carried out by the principal through class observation supervision.